PENGOLAHAN LIMBAH PLASTIK SEBAGAI MATERIAL PAVING BLOCK DI DESA SENANGGALIH, LOMBOK TIMUR - Ramadhan, Syahrin; Alif, Ardan; Hardina, Lufika; Maulana, Affan (Universitas Mataram, 2025)
Plastic waste is a serious problem faced by various regions, one of which is Senanggalih Village, Sambelia District, East Lombok Regency. Poorly managed plastic waste has impacted public health and environmental pollution. This condition indicates the need for innovation that can transform plastic waste into something economically valuable and environmentally friendly. This community service activity aims to educate the community about the dangers of plastic waste and provide training in managing this waste into a useful product, namely paving blocks. The service method used is participatory training that involves various components of the Senanggalih Village community such as the Family Welfare Movement (PKK), youth organizations, residents and village staff. The implementation began with observing the condition of plastic waste, delivering materials, and then practicing making paving blocks from a mixture of melted plastic, oil, and sand. The implementation results in increased knowledge of the participants about the dangers of plastic waste and skills in processing the waste into paving blocks. As many as 90% of participants were able to understand the manufacturing process and expressed a desire to continue this recycling effort. Thus, this community service is not only able to provide a solution to the plastic waste problem, but also provides an opportunity to create new businesses based on waste management in Senanggalih Village.